Bendamustine Associated with Irreversible Ascending Paralysis - Ashraf Alhafez; Omar S. Aljitawi; Tara L. Lin; Siddhartha Ganguly; Sunil Abhyankar; Joseph P. McGuirk (Case Reports in Hematology)
Bendamustine is an alkylating agent currently used in the treatment of lymphoproliferative disorders. Many adverse effects, including a rare case of reversible neurotoxicity, have been reported in association with bendamustine. Herein, we report the first case of irreversible ascending paralysis related to bendamustine.